A influência da estereoscopia na experiência imersiva nos videogames - Gonçalves, Diogo Augusto (2015)
Stereoscopy is a form of image reproduction older than photography itself, and unlike it, it rearranges the spatiality of the elements in the screen, allowing observers different points of view. Although stereoscopy being a form of visualization this old, it did not remain obsolete. It has been reinvented nowadays with the help of different reproduction techniques. Stereoscopy expanded to the cinema, and recently for television and videogames. Regarding stereoscopy, this dissertation proposes to address how the tridimensional perspective influences the immersive experience in videogames, leading the virtual space of the game, closer to the interactor, which ultimately creates an intimate relationship between those two agents, giving new meanings to the interaction. Thus, for the development of this research, it was necessary to survey the historical evolution of stereoscopy, videogames and devices that enable immersion through virtual reality, to understand how this evolution happened and which was the motivation that led to this demand. After this historical overview, this research proposes to present what are the features that make the act of playing a video game something so immersive that sensitizes players to try new experiences. At last, we analyze games that use stereoscopy as a feature that enables enhanced immersion in their experiences, in order to understand the strategies that these games use to strengthen the link between the interactor and the fantastic interactive worlds, making a survey of the main characteristics that are aggregated to these games.